Intraductal Oncocytic Papillary Neoplasm of the Pancreas: A Case of a Second Neoplasm in a Pancreas Cancer Survivor - Garg, Mrinal S; Schuerle, Theresa; Liu, Yulin; Thakkar, Shyam J (JOP. Journal of the Pancreas, 2015)
Context Cystic neoplasms, which are less common forms of exocrine pancreatic neoplasms, consist of mainly intraductal papillary mucinous neoplasms (IPMN) and mucinous cystic neoplasms. Mucinous cystic neoplasms, unlike IPMN, are not associated with ductal growth, are usually multilocular in nature, and have ovarian type stroma. Mucinous cystadenocarcinoma is a type of mucinous cystic neoplasm more commonly found in women. Intraductal oncocytic papillary neoplasms of the pancreas are the least common variant of IPMN. Despite this classification, intraductal oncocytic papillary neoplasms have been compared to mucinous cystic neoplasms in previous studies and the classification is still questioned. Case report We report a rare case of an intraductal oncocytic papillary neoplasm of the pancreas occurring in a 52-year-old male with a prior history of surgically excised mucinous cystadenocarcinoma. This is the first known case of an intraductal oncocytic papillary neoplasm occurring after a prior pancreatic neoplasm. Conclusions As the diagnosis of intraductal oncocytic papillary neoplasms are rare, having only a few case reports and small series on which to understand its disease process, it is imperative to discuss each case and detail possible correlations with other pancreatic cystic neoplasms as well as distinctions from its current association within IPMN. Image: Pathology of intraductal oncocytic papillary neoplasm.